Uncommoditizing strategies by emerging market firms. Issue 2 (15th July 2019) - Cuervo-Cazurra, Alvaro; Carneiro, Jorge; Finchelstein, Diego; Duran, Patricio; Gonzalez-Perez, Maria Alejandra; Montoya, Miguel A.; Borda Reyes, Armando; Fleury, Maria Tereza Leme; Newburry, William
Abstract : Purpose: This paper aims to analyze how emerging market firms upgrade their capabilities by focusing on "uncommoditizing strategies" that enable them to achieve levels of international competitiveness beyond the comparative advantages of their home countries and serve markets with premium pricing, quality and reputation of products. Design/methodology/approach: In this paper, the authors studied 18 Latin American companies across six countries. Latin America represents an ideal setting because many of these countries have traditionally developed using natural resource endowments, and their firms have tended to rely on these in their internationalization. To facilitate the analysis of each case and the comparisons across cases, the authors used the same analytical framework for the companies, identifying the sources of differentiation and cost efficiency strategies that enabled these firms to upgrade their capabilities and compete on the basis of premium pricing, quality and reputation. Findings: The analysis identified a general framework that represents an abstraction of the actions taken by these companies over time. The proposed model consists of three main elements used to pursue uncommoditizing strategies: tropicalized innovation, global efficiency and coordinated control. Originality/value: Recent research on emerging market firms has shown interest in how these firms upgrade their capabilities. This paper contributes to this stream of research by providing an overarching framework that not only bridged previous narrower studies but also explained how firms can develop uncommoditizing strategies to upgrade their capabilities. Further, this paper helps managers by providing a comprehensive yet succinct overview of the main strategies that they can use to help their firms to achieve international competitiveness.